Selective serotonin reuptake inhibitors (SSRIs) prevent meta-iodobenzylguanidine (MIBG) uptake in platelets without affecting neuroblastoma tumor uptake - Blom, Thomas (EJNMMI Res, 2020)
BACKGROUND: The therapeutic use of [(131)I]meta-iodobenzylguanidine ([(131)I]MIBG) is often accompanied by hematological toxicity, mainly consisting of persistent and severe thrombocytopenia. While MIBG accumulates in neuroblastoma cells via selective uptake by the norepinephrine transporter (NET), the serotonin transporter (SERT) is responsible for cellular uptake of MIBG in platelets. In this study, we have investigated whether pharmacological intervention with selective serotonin reuptake inhibitors (SSRIs) may prevent radiotoxic MIBG uptake in platelets without affecting neuroblastoma tumor uptake. METHODS: To determine the transport kinetics of SERT for [(125)I]MIBG, HEK293 cells were transfected with SERT and uptake assays were conducted. Next, a panel of seven SSRIs was tested in vitro for their inhibitory potency on the uptake of [(125)I]MIBG in isolated human platelets and in cultured neuroblastoma cells. We investigated in vivo the efficacy of the four best performing SSRIs on the accumulation of [(125)I]MIBG in nude mice bearing subcutaneous neuroblastoma xenografts. In ex vivo experiments, the diluted plasma of mice treated with SSRIs was added to isolated human platelets to assess the effect on [(125)I]MIBG uptake. RESULTS: SERT performed as a low-affinity transporter of [(125)I]MIBG in comparison with NET (K(m) = 9.7 μM and 0.49 μM, respectively). Paroxetine was the most potent uptake inhibitor of both serotonin (IC(50) = 0.6 nM) and MIBG (IC(50) = 0.2 nM) in platelets. Citalopram was the most selective SERT inhibitor of [(125)I]MIBG uptake, with high SERT affinity in platelets (IC(50) = 7.8 nM) and low NET affinity in neuroblastoma cells (IC(50) = 11.940 nM). The in vivo tested SSRIs (citalopram, fluvoxamine, sertraline, and paroxetine) had no effect on [(125)I]MIBG uptake levels in neuroblastoma xenografts. In contrast, treatment with desipramine, a NET selective inhibitor, resulted in profoundly decreased xenograft [(125)I]MIBG levels (p < 0.0001). In ex vivo [(125)I]MIBG uptake experiments, 100- and 34-fold diluted murine plasma of mice treated with citalopram added to isolated human platelets led to a decrease in MIBG uptake of 54–76%, respectively. CONCLUSION: Our study demonstrates for the first time that SSRIs selectively inhibit MIBG uptake in platelets without affecting MIBG accumulation in an in vivo neuroblastoma model. The concomitant application of citalopram during [(131)I]MIBG therapy seems a promising strategy to prevent thrombocytopenia in neuroblastoma patients.